Avaliação do potencial condroprotetor da molécula rLosac em modelo inflamatório, in vitro, induzido pela interleucina 1β - Pereira Junior, Edgard dos Santos [UNIFESP] (2016)
Background: Osteoarthritis is an articular disease more prevalent, resulting in the progressive deterioration of the articular cartilage, mediated by proinflammatory pathways of the innate immunity and the production of cytokines. The use of chondroprotective drugs can slow the process of deterioration joint although its effectiveness is questionable. rLosac is a cytoprotective adhesion molecule from the caterpillar Lonomia obliqua. Purpose: To evaluate the chondroprotective potential of rLosac in fibrochondrocytes. Methods: The primary culture of fibrochondrocytes were obtained from rat knee meniscus, grown in two conditions: serum deprivation or in the presence os 10ng/mL interleukin 1β and then treated with rLosac. Various parameters were measured: cell viability, cell cycle and apoptosis by flow cytometry, release of nitric oxide, and protein expression of extracellular matrix molecules. Results: rLosac was able to increase proliferation of fibrochondrocytes and to inhibit apoptosis induced by serum deprivation. In the presence of 10 ng/mL IL-1β, rLosac caused reduction of nitric oxide release and matrix metalloproteinases 2 and 9 activities, and preservation of the extracellular matrix components such as type II collagen, fibronectin and laminin. Conclusions: rLosac is able to induce cell proliferation in fibrochondrocytes and to prevent cell death induced by serum deprivation or in the presence of interleukin 1β, modulating cell cycle and increasing cell survival, reducing nitric oxide release and the activity of metalloproteinases 2 and 9, besides to preserve extra cellular matrix